The Effect of Service Quality on Customer Satisfaction and Trust in Using Tokopedia Services - Yulita Fairina Susanti; Devi Juliani (ADI Publisher, 2020)
The development of internet users encourages a great potential for the creation of online shopping. Consumers have several factors considered in making online purchasing decisions through an electronic market. This is because one of the problems in online sales in Indonesia is the difficulty in building buyer trust. However, customer satisfaction level towards Tokopedia site is relatively low due to the high level of complaints, specifically the one that is provided by its customer service that is deemed to be very slow in responding the complaints. The aim of this study is to find out the effect of service quality on customer satisfaction, service quality on consumer trust, and customer satisfaction on consumer trust in utilizing Tokopedia services. This study used a quantitative approach with a casual type. The sample used was 100 users who use Tokopedia services. The analysis technique used in this study is Structural Equation Modeling (SEM) Partial Least Square (PLS), with the help of SmartPLS program. The results showed that Service quality has a positive effect on customer satisfaction, Service quality has a positive effect on trust, and customer satisfaction has a positive effect on trust.